2016
DOI: 10.1186/s12887-016-0734-3
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical physiological responses to propranolol in a Rett syndrome patient: a case report

Abstract: BackgroundRett Syndrome (RTT), caused by a loss-of-function in the epigenetic modulator: X-linked methyl-CpG binding protein 2 (MeCP2), is a pervasive neurological disorder characterized by compromised brain functions, anxiety, severe mental retardation, language and learning disabilities, repetitive stereotyped hand movements and developmental regression. An imbalance in the sympathetic and the parasympathetic nervous system (dysautonomia) and the resulting autonomic storms is a frequent occurrence in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Heart rate variability (HRV) is an indirect measure of autonomic arousal [ 89 , 90 ] and can be measured using wearable sensor technology. Wearable sensor technology has been used as a biometric proxy measure to monitor treatment outcomes of EBAD in RTT [ 40 , 91 ] and in those with other complex neurodevelopmental disorders [ 92 ]. In these cases, sensor-based biometrics can assist in the individualisation of patient care allowing the management of patients with EBAD.…”
Section: Emotional Behavioural and Autonomic Dysregulation In Rttmentioning
confidence: 99%
“…Heart rate variability (HRV) is an indirect measure of autonomic arousal [ 89 , 90 ] and can be measured using wearable sensor technology. Wearable sensor technology has been used as a biometric proxy measure to monitor treatment outcomes of EBAD in RTT [ 40 , 91 ] and in those with other complex neurodevelopmental disorders [ 92 ]. In these cases, sensor-based biometrics can assist in the individualisation of patient care allowing the management of patients with EBAD.…”
Section: Emotional Behavioural and Autonomic Dysregulation In Rttmentioning
confidence: 99%
“…Autonomic dysregulation is likely to be a critical driver for the diverse symptoms exhibited by patients with RTT. The autonomic component can be exploited and targeted therapeutically using biometricguided therapy to manage EBAD in patients with RTT 15,16 and in those with multi-comorbid neurodevelopmental disorders. 17 This is important given that the autonomic component of EBAD is pervasive and has widespread effects on multiple overlapping systems.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in EDA could also provide useful information on seizures since when compared to adults, children with epilepsy were found to have a higher EDA response (36). We have previously shown that the EDA is disordered in RTT patients (61,62). In our recent evidence synthesis (59), we proposed that EDA could also be useful in monitoring the physical health of the patient, and we can now extend its use to provide valuable information on the sympathetic response in RTT patients who are more prone to frequent seizures.…”
Section: Discussionmentioning
confidence: 99%